Analysis of the light performance of Chinese solar greenhouse with internal insulation based on a solar radiation model - Sun, Qian; Song, Yang; Yang, Zhigang; Liu, Xiaorui; Cui, Shimao (Frontiers in Energy Research, 2023)
Chinese solar greenhouses are important agricultural building facilities with highly efficient and sustainable solar energy consumption. A solar greenhouse with an external insulation blanket for heat preservation is the most prevalent type of CSG. However, greenhouse performance degrades as the thermal insulation performance of the external blanket deteriorates over time when the blanket is exposed to harsh environmental conditions. Moreover, the external blanket is usually parked in an inconvenient location on the south roof in the practice, resulting in shading owing to its increasing coverage length. This significantly influences the solar radiation received by the south roof and that projected on the wall, ultimately affecting the light performance of the greenhouse. Therefore, a solar greenhouse with an innovatively applied internal insulation system was proposed in this study. To analyze the light performance of the solar greenhouse, a solar radiation model was established and verified by comparing the measured and calculated values. Based on the calculated model results, the spatial distribution of solar radiation inside the greenhouse and its allocation to the interior surfaces of the greenhouse were simulated. The total captured and transmitted solar radiation accumulations were compared for three different roof shapes. The captured and transmitted radiation accumulation of the greenhouse with internal insulation increased by 3.9–9.5 and 1.8–4.4 MJ compared to the two other greenhouses, respectively. The effect of the position of the parked blanket on the beam solar radiation projected on the wall and ground was considered. The results indicated that the increased blanket coverage length decreased the cumulative radiation on the wall by 25.24%–99.82%, which did not contribute to improving greenhouse energy-saving production. This study provides a new approach to greenhouse design and optimization.